Pengaruh Fermentasi Terhadap Kelimpahan Lactobacillus sp. Dalam Probiotik Limbah Cair Tahu - Hidayat, Fajar; Raden Kokoh Haryo Putro (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Tofu wastewater is a liquid waste with high organic content that has the potential to be recycled. This study aims to analyze the effect of substrate composition and fermentation time using EM4 starter on the abundance of Lactobacillus sp. as a key parameter of probiotic quality. The study used a Completely Randomized Design (CRD) with four composition treatments: P1 (30% TWW : 30% water : 40% EM4), P2 (40% TWW : 20% water : 40% EM4), P3 (50% TWW : 10% water : 40% EM4), and P4 (60% TWW : 0% water : 40% EM4). Fermentation was observed for 18 days. The results showed that composition and fermentation time significantly affected bacterial abundance. The highest abundance was achieved in P4 on day 14 (7.0 × 10⁶ CFU/mL). However, the most efficient composition was P1, which produced a high abundance of Lactobacillus sp. (4.1 × 10⁶ CFU/mL) and successfully reduced BOD₅ levels to 108.45 mg/L, below the quality standard. The optimal fermentation time was 14 days, after which the population declined. It was concluded that the fermentation of tofu wastewater with the right composition and time can produce qualified probiotics while reducing environmental pollution.